(untitled) (World Bulletin of Management and Law, 2024)
The article substantiates the importance of developing a quality management system for textile and sewing-knitting industry enterprises in the digital economy, improves methods for its assessment, and, based on the analysis, develops a strategy and model for the development of a quality management system.